THE INFLUENCE OF TALENT MANAGEMENT AND KNOWLEDGE MANAGEMENT ON EMPLOYEE PERFORMANCE WITH EMPLOYEE ENGAGEMENT AS AN INTERVENING VARIABLE AT THE MALUKU PROVINCIAL TRANSPORTATION DEPARTMENT - Alfath Zulfanur Abadi; Chonchita Valentina Latupapua; Novalien Carolina Lewaherilla (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study examines the impact of Talent Management (TM) and Knowledge Management (KM) on Employee Performance (EP), with Employee Engagement (EE) as a mediating variable, within the context of the Maluku Provincial Transportation Department. Using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method, this research analyzes both direct and indirect relationships among these variables. The findings indicate that TM has a positive and significant effect on EP, demonstrating that strategic talent acquisition, competency development, and career planning enhance employee productivity. Conversely, KM does not directly influence EP, suggesting that knowledge-sharing mechanisms alone are insufficient to improve performance outcomes. However, mediation analysis reveals that EE plays a crucial role in strengthening both TM-EP and KM-EP relationships, highlighting the necessity of engagement-driven frameworks to maximize talent and knowledge utilization. Furthermore, EE exhibits a strong positive effect on EP, reinforcing the importance of fostering workplace motivation, participation, and job satisfaction. These results provide valuable insights for public sector HR management, emphasizing the need for policy reforms that integrate talent retention, structured learning initiatives, and engagement-driven leadership strategies. Given the increasing demands for efficiency and workforce optimization in government institutions, adopting TM, KM, and EE-based HR models will be instrumental in enhancing employee performance and ensuring long-term institutional success.